1984
DOI: 10.1159/000280980
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of the Secretion from the Prostatic Gland in Cases of Reduced Fertility

Abstract: The efficiency of Pygenum africanum treatment was tested on a population where the acid phosphatase activity was shown to be reduced at two successive examinations. The treatment caused an increase in acid phosphatase activity and total protein secretion. However, the fact that the men who had IgA present in their ejaculate reacted more favorably to the treatment shows that Pygenum africanum is more efficient in cases where there is no prostate gland inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A significant increase in the alkaline phosphatase level was observed in the animals treated with T. glaberrima. The enzyme ALP was found to increase the prostatic secretions and helps to maintain the appropriate pH of seminal fluid, which in turn is necessary for retaining the sperm motility (Lucchetta et al, 1984;Clavert et al, 1986;Carani et al, 1991). Thus, the plant T. glaberrima may be an effective therapy for male infertility, especially in cases of diminished prostatic secretions.…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase in the alkaline phosphatase level was observed in the animals treated with T. glaberrima. The enzyme ALP was found to increase the prostatic secretions and helps to maintain the appropriate pH of seminal fluid, which in turn is necessary for retaining the sperm motility (Lucchetta et al, 1984;Clavert et al, 1986;Carani et al, 1991). Thus, the plant T. glaberrima may be an effective therapy for male infertility, especially in cases of diminished prostatic secretions.…”
Section: Discussionmentioning
confidence: 99%
“…Like Serenoa repens, it improves a variety of urinary symptoms such as urinary frequency, nocturia, flow interruption, after-dribbling, weak stream, and hesitation [128]. Additionally, pygeum increases prostatic secretions and improve the composition of the seminal fluid [129], besides raising patient's capacity to achieve erections [130].…”
Section: (C)mentioning
confidence: 99%
“…Sperm motility is affected by the pH of prostatic fluid and some studies have demonstrated a beneficial effect of pygeum on prostatic fluid pH. 47,48 In addition to this effect, pygeum has been shown to be useful for treating prostatitis and BPH. A study of men with these conditions who also had additional sexual disturbance as a result showed that subjects who were treated with an extract of 200 mg per day of pygeum had improvements.…”
Section: Pygeummentioning
confidence: 99%